Residency and migratory behaviour by adult Pomatomus saltatrix in a South African coastal embayment - Hedger, R.D.; Næsje, T.F.; Cowley, P.D.; Thorstad, E.B.; Attwood, C.; Økland, F.; Wilke, C.G.; Kerwath, S. (Estuarine, coastal and shelf science, 2010)
Acoustic telemetry was used to study patterns of habitat use and movements of Pomatomus saltatrix L. (common name elf/shad/bluefish/tailor) within the Saldanha Bay with Langebaan Lagoon coastal embayment on the west coast of South Africa. Thirty six mature P. saltatrix were tagged with acoustic transmitters and released within the lagoon in May 2006 and November–December 2007, and their positions were monitored until late-November 2008 using 28 hydrophones positioned throughout the embayment. The detection pattern of P. saltatrix suggested a tendency to residence within the embayment throughout the thirty month long study period, with nearly 60% of released individuals only being detected within the lagoon in the inner part of the embayment. However, there was a long-term trend of movement from the lagoon into the bay. One individual was recaptured off the east coast of South Africa 21 months after being tagged, 1760 km away, suggesting that P. saltatrix are capable of undertaking long along-shore migrations. Over finer scales within the inner lagoon, P. saltatrix ground speed increased (1) with an increase in tidal current speed, (2) with an increase in photoperiod, and (3) during day. Pomatomus saltatrix tended to move seaward during ebb tides, and to occupy greater depths during day.